Parent's Attitudes towards Physical Education of Preschool Children - Radovan B. Grandić; Marta D. Dedaj; Tanja P. Panić (University of Belgrade, Teacher Education Faculty, 2018)
Humanistic concept of physical education is based on meeting essential and existential needs of every child. The primary goal of physical education is to develop a habit of regular physical exercise in children. The development of this habit is not only the task of physical education in preschool institutions and primary schools, but also of the family. The goal of this research was to examine parents' attitudes towards physical education of preschool children. The research was conducted on a sample of 153 parents of children attending a preschool institution in the city of Novi Sad. The results indicate that parents have a positive attitude regarding the importance of physical education of the preschool children. What gives rise to concern is the data showing the small amount of time that parents and children devote to physical activity on a regular basis. Our conclusion is that it is necessary to increase the scope of physical activity of preschool children, given that regular physical exercise and involvement in sports activities can positively influence the socialization of children. It is important to develop in children the love of physical education and a healthy lifestyle even before they start school, and the example set by parents can be very inspirational in achieving this goal.